2023
DOI: 10.4102/hts.v79i1.8020
|View full text |Cite
|
Sign up to set email alerts
|

Qanun, religious education, religiosity and sexual activity among Muslim youth

Abstract: Muslim youths must shun free sexual behaviours. However, these actions are highly prevalent, especially among the Muslim youth. This study aimed to determine the effect of qanun (local regulations based on Islamic law), religiosity and religious education on the sexual activity of Muslim youth. The study used a case-control design carried out in the province of Aceh, which applies the qanun, and in the province of North Sumatra, which does not apply the qanun. Researchers interviewed 552 Muslim youths using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…It is corroborated by Unser, who mentioned that religious values contribute to forming children's existence in the modern context 32 . The same thing was also given by Muhibbuthabry et al, who found the impact of children's religiosity contributed to reducing the impact of promiscuity 33 . The cultivation of religious values determined through the example of praying is part of the cultivation of the Islamic identity that the Prophet wants to show.…”
Section: The Virtues Of Family In the Context Of Modern Societysupporting
confidence: 61%
“…It is corroborated by Unser, who mentioned that religious values contribute to forming children's existence in the modern context 32 . The same thing was also given by Muhibbuthabry et al, who found the impact of children's religiosity contributed to reducing the impact of promiscuity 33 . The cultivation of religious values determined through the example of praying is part of the cultivation of the Islamic identity that the Prophet wants to show.…”
Section: The Virtues Of Family In the Context Of Modern Societysupporting
confidence: 61%
“…Sexual behavior in adolescents can be influenced by the family environment. Guidance from parents is very important because adolescents are still looking for themselves, and if there is no supervision and education by parents, then they will fall into negative things (Muhibbuthabry et al, 2023). Puberty education is an important form of education and skill to help parents and adolescents navigate adolescents' physical, emotional, and interpersonal changes with positive outcomes (Koirala, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers consider three characteristics of spirituality-hope, activity, and connection with oneself, the world, and others-as determinants of physical and mental health in individuals (Habibollahi et al, 2018). Other studies indicate that adolescents who believe in God and consider the role of religion important in their lives engage less in risky behaviors such as risky sexual relationships and substance abuse compared to their non-religious peers (Muhibbuthabry et al, 2023).…”
Section: Introductionmentioning
confidence: 99%